Evaluation and analysis on existing sanitary landfill's liner and leachate collection systems - Bausah, A. (University Malaysia Sarawak (UNIMAS), 2006)
This study was conducted to investigate the effectiveness of using the TRISOPLAST layer in Mambong and geocomposte layer in Bekenu to prevent the absotption of leachate into the underground water. This study also investigates the design of the leachate channel system and the treatment plan for both sites. This study would be able to determine whether both centres can operate efficiently or not in Malaysia where heavy rainfall is received annually.